Personal Branding Pustakawan Di Perpustakaan - Rina Handayani (Pustakaloka, 2015)
Using technology people introduce themselves into a brand, a  community  could  accept  them  without  any  complicated  process. Librarians as supporting the development of libraries in an institution that requires a personal branding good on him, it is to change the public image of a librarian. Using theoretical approach this study dealts with a response to Personal branding of Librarian. This study argues that the presence of the Personal branding will defnitely have a big impact on the Library. A library that has a good image in the world will certainly be able to develop the programs to increase the support of its librarian Personal  branding. So  that  the  realization  of Personal  branding,  this institution will supports a good image.